2014
DOI: 10.1111/aos.12510
|View full text |Cite
|
Sign up to set email alerts
|

Expression of cytokines on the iris of patients with neovascular glaucoma

Abstract: ABSTRACT.Purpose: To determine the expression levels of cytokines, including growth factors, inflammatory cytokines, and cell migration associated factors on the iris from subjects with neovascular glaucoma (NVG). Methods: After receiving formal consent from 12 subjects with NVG secondary to proliferative diabetic retinopathy and 12 subjects with primary open angle glaucoma (POAG), trabeculectomy was performed and iris specimens were collected during the surgery. Each subject with NVG received intravitreal inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Thus, there are many different retinal gene therapy strategies in the pipeline, including gene augmentation, knockdown, gene editing, delivery of neurotrophic factors, and delivery of reagents, which modulate pathways controlling oxidative stress, neovascularization, or metabolism. [23][24][25][26][27] In addition, there has been an expansion of the ''vector toolkit,'' with the goal of enhancing and facilitating delivery of gene-based treatments to the appropriate cell types and through different delivery routes. [28][29][30][31][32] Proof-of-concept studies in mouse models have shown that some of these vectors can be used to treat different inherited retinal degenerative diseases using gene augmentation or optogenetic strategies and through different routes of delivery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, there are many different retinal gene therapy strategies in the pipeline, including gene augmentation, knockdown, gene editing, delivery of neurotrophic factors, and delivery of reagents, which modulate pathways controlling oxidative stress, neovascularization, or metabolism. [23][24][25][26][27] In addition, there has been an expansion of the ''vector toolkit,'' with the goal of enhancing and facilitating delivery of gene-based treatments to the appropriate cell types and through different delivery routes. [28][29][30][31][32] Proof-of-concept studies in mouse models have shown that some of these vectors can be used to treat different inherited retinal degenerative diseases using gene augmentation or optogenetic strategies and through different routes of delivery.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ciliary body transduction may be useful for delivering stable supplies of diffusible molecules that could be used to treat a variety of different diseases, including wet AMD, and AAV7m8 could be useful in strategies involving diffusible agents such as neurotrophic factors, antioxidants, nutrients, antibodies, or even compounds that could modulate intraocular pressure. [23][24][25][26] Transduction of these structures, however, could also have an impact on safety. It is possible that transduction of anterior segment structures is partially responsible for immunologic/inflammatory sequelae that were apparent after high-dose IVI of AAV7m8.…”
Section: Discussionmentioning
confidence: 99%
“…[2,3] The mechanism underlying NVG in proliferative DR (PDR) is mainly mediated by various cytokines and enzymes induced by retinal ischemia and inflammation. [4,5] The most suspected and studied cytokine is vascular endothelial growth factor (VEGF), and anti-VEGF agents have been used to treat various diseases involving retinal ischemic conditions such as PDR. [6] Treatments for PDR patients, including panretinal photocoagulation (PRP), vitrectomy, and anti-VEGF agents, are targeted to reduce cytokine levels in the vitreous.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence has suggested that inflammatory processes play a major role in the pathogenesis of DR, 4 , 5 neovascular glaucoma (NVG) associated with DR, 6 and age-related macular degeneration. 7 Studies including ours 8 , 9 have demonstrated that MCP-1, IL-6, IL-8, and VEGF are the 4 major inflammatory cytokines that are upregulated in eyes with PDR.…”
Section: Introductionmentioning
confidence: 99%